Polyploid Cells in Human Leukocytes Following in vivo and in vitro Irradiation - Ishihara, Takaaki; Kumatori, Toshiyuki (CYTOLOGIA, 1966)
Incidence of polyploid cells were studied in leukocyte cultures established from radiation-exposed people, as well as from human blood irradiated in vitro with 60Co at the dose from 50 r to 350 r. Polyploid cells were extremely frequent in the radiation-exposed subjects than in the normal ones. A high frequency of polyploid cells was also obtained in leukocytes cultured from the blood irradiated in vitro. The frequency of polyploid cells increased with the dose of radiation. The majority of the polyploid cells contained abnormal chromosomes such as dicentrics, tricentrics, rings, some other related ones, and acentric fragments. Among them dicentrics were most frequent in occurrence. The frequency of polyploid cells showing chromosome abnormalities increased with the dose of radiation. Very often the abnormal chromosomes were present in pair, as a set of two morphologically identical chromosomes, in most cells lying in the tetraploid range; while they occurred in two pairs in cells in the octoploid range. Evidence presented is suggestive of that the polyploid cells might be originated from affected cells with abnormal chromosomes such as dicentrics as may interfere with cell division, the distribution of chromosomes to the daughter cells being omitted after chromosome replication.